2007
DOI: 10.1002/app.26223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the copolymer architecture and composition on the response and mechanical properties of pH‐sensitive fibers

Abstract: A series of copolymers based on acrylonitrile (AN) and acrylic acid (AA) with varying architecture and composition were synthesized using free radical polymerization. The distribution of monomers in the copolymer chains could be successfully controlled by regulating the addition of more reactive monomer (AA). Copolymers having nearly random distribution of comonomer moieties to block type distribution with different composition (10-50 mol % AA) were synthesized to investigate the effect of polymer architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The above approach could produce copolymers where the distribution of the comonomer moieties could be controlled to a great extent giving rise to a block type copolymer. The structure and properties of these block type copolymers in comparison to their random counterparts have been reported earlier 14, 15. The quantitative analysis of 13 C NMR proved that there was significant increase in the concentration of segmented acrylonitrile and acrylic acid moieties compared to the random structure using the modified polymerization approach.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The above approach could produce copolymers where the distribution of the comonomer moieties could be controlled to a great extent giving rise to a block type copolymer. The structure and properties of these block type copolymers in comparison to their random counterparts have been reported earlier 14, 15. The quantitative analysis of 13 C NMR proved that there was significant increase in the concentration of segmented acrylonitrile and acrylic acid moieties compared to the random structure using the modified polymerization approach.…”
Section: Resultssupporting
confidence: 58%
“…Our recent experiments have shown that the formation of domain morphology was in fact possible and the resultant fiber is stronger than the fibers produced from random copolymers. Also, the acrylic acid domains could provide faster diffusion of water to give larger and rapid swelling and deswelling under suitable pH 14, 15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of reversible dilation and contraction by changing the state of ionization of polymers have been the subject of pioneering work . Several papers regarding the sensitivity of polyacrylonitrile copolymers have been published recently . These works show that the fibre diameter, spinning conditions and post‐spinning operation, such as heat‐setting temperature, as well as the distribution of monomer moiety, have a significant effect on the pH response of P(AN/AA) copolymer.…”
Section: Resultsmentioning
confidence: 99%